Defect Detection in Grouting Sleeve Grouting Material by Piezoelectric Wave Method - Qiyun Qiao; Xiuyu Wang; Wenchao Liu; Hongchun Yang (Buildings, 2024)
The construction defects in grouting sleeves can jeopardize the safety of precast reinforced concrete structures. Thus, efficient and accurate defect detection is critical in engineering construction. In this paper, a defect detection method based on piezoelectric wave theory was proposed. Two piezoelectric ceramics were arranged within the grouting sleeve. One piezoelectric ceramic was affixed on the top of the steel bar, while the other was embedded in the grouting material, serving as the driver and sensor, respectively. The compactness defects, air cavity defects, steel anchoring defects, and water–binder ratio defects were set in the grouting sleeves, and the trends in time domain signals and signal evaluation indicators based on the wavelet packet total energy value (WPTEV) of different specimens were investigated. Based on the WPTEV, the evaluation index (EI) was proposed. In addition, the effect of the grouting material’s age on the piezoelectric wave signal was verified. Furthermore, the influence of grouting material defects on signals was simulated in ABAQUS, and the time domain signals and wavelet packet energy of sensor signals for specimens with varying defect dimensions were evaluated. The results showed that: (1) The defects in the grouting materials reduced the stress waves propagated through the grouting materials, resulting in a decrease in attenuation and an increasing trend in the signal; (2) The peak-to-peak values of piezoelectric ceramic sensors and the WPTEV of the signal increased with the degree of defects, and the WPTEV was more pronounced. For specimen M68, the WPTEV was 3.3 times that of the healthy specimen, however, the peak-to-peak value was only 2.3 times that of the healthy specimen; (3) The degree of defects was accurately determined by the defect evaluation index (EI) based on the WPTEV; (4) The signal was significantly attenuated with the increase in the age of the grouting material, especially in the first three days, and finally the signal achieved a stable value; (5) The numerical simulation indicated that the defects in the length and thickness of the air cavity in the grouting material were efficiently detected by the proposed piezoelectric arrangement in this study.